Development of Project Based Learning E-Modules with Local Wisdom Content in Grade IV Science Lessons (IPAS) - Delimanugari, Daluti (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2024)
This research is based on developing a learning media product. E-modules developed to meet the needs of learning resources. The objectives and significance of this research to understand the entire procedure of developing project-based E-modules with local wisdom content for Grade IV Natural and Social Sciences in MI/SD. The process of creating the e-modules should be explained in detail, based on the type intended for use in the research. This will allow us to determine the suitability of the e-module product, making it useful for teachers and students who utilize the product. Secondly, to ascertain the responses provided by both teachers and students when using the project-based E-module product with local wisdom content. These responses will be valuable in assessing students' interest in self-directed learning using the product. Additionally, understanding teachers' responses when using the product can facilitate the teaching process and address any challenges that arise. Therefore, this research aims to uncover the responses generated. This e-module is expected to be able to attract attention and be independent in learning so as to add to the learning experience and have knowledge about local wisdom in the area. This study uses a development research design, which uses the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The results of the study show that the results of the validation trials of media experts and material experts mean that the average percentage score is 77% with valid criteria used but needs revision. The results of user trials get a percentage score of 82.4% with valid criteria used but need revision.